Willy Wonka & the chocolate factory - Dahl, Roald; Wilder, Gene, 1935-; Albertson, Jack, 1910-1981.; Ostrum, Peter, 1957-; Stuart, Mel.; Margulies, Stan.; Wolper, David L.; Wolper Pictures (Firm); Quaker Oats Company; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 1996)
Join Charlie Bucket, his grandfather, and four lucky contest winners on a tour through the factory of the mysterious candy mogul Willy Wonka.
Title on container front: 25th Anniversary - David L. Wolper presents "Willy Wonka & the Chocolate Factory".
VHS Hi-Fi format.
Rated G.
Videocassette release of the 1971 motion picture.
Based on Charlie and the chocolate factory by Roald Dahl.
Director, Mel Stuart ; producers, Stan Margulies and David Wolper ; screenplay, Roald Dahl ; lyrics and music, Leslie Bricusse, Anthony Newley.
Keywords: Humorous stories -- Juvenile literature; Problem solving -- Juvenile films; Human behavior -- Juvenile films; Children's films; Feature films, Juvenile; Motion pictures, Juvenile